PEMANFAATAN BUAH NIPAH SEBAGAI BAHAN PEMBUATAN FRUIT LEATHER DENGAN PENAMBAHAN KULIT BUAH NAGA MERAH - Romi Erdiyus; Usman Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aimed to getthe best ratio of mesocarpnypafruit and red dragon fruitpeelto produce good quality of the fruit leather with attractive colors for food diversification. This study useda Completely Randomized Design with 4 treatments and 4 replications thus obtaining 16 experimental units the treatments were, the ratio of mesocarpnypafruit and red dragon fruit peel with treatments,NH1 (65:35), NH2 (60:40), NH3 (55:45) and NH4 (50:50). The data obtained were statistically analyzed using Analysis of Variance (ANOVA).Jika F hitung lebih besar atau sama dengan F tabel maka dilanjutkan dengan uji DNMRT pada taraf 5%.If the  F count was greater than or equal to F table then continued with Duncan New Multiple Range Test at 5% level.The resultsof the present study indicate that ratio of mesocarpnypa fruitand red dragon fruit peelsignificantly affected to the moisture content (9.14-11.50%), ash (0.78-0.91%), initialdegree of acidity (5.20-5.28) and total sucrose (30.55-42.55%). Based on the resultsof sensory evaluation show that the dragon fruit peel significantly affected to the color, aroma, taste, texture, and overall the value of panelists for hedonic test were “rather like to like”for this fruit leather. The best treatment based on the water content, ash content, initialdegree of acidity, total sucrose andsensory evaluation was treatmentNH1 (65% mesocarpnypafruit and 35% red dragon peel). Keywords:Fruit leather, mesocarp nypa fruit and red dragon peel.